Housing single-sheet material: ‘Fisherizing’ at the Bodleian Library, Oxford - Honey, A (Institute of Conservation (Icon), 2004)
‘Fisherizing’ is one approach to the housing of single-sheet material that has been adopted at the Bodleian Library, Oxford. It is a system of binding modern papers of predominantly uniform format, typescripts for example, which are unsuitable for either fasciculing or other binding methods and which require more protection than that offered by archive folders. The technique was named after H.A.L. Fisher, a twentieth-century Oxford historian, whose papers were donated to the Bodleian Library in 1958. Fisherizing was developed between 1985 and 1987 when Fisher’s papers were treated. The original fisherizing technique has recently been reviewed and further refinements have been introduced.